Carriage of Goods in Swiss Maritime Law - Vesna Polić Foglar (Poredbeno Pomorsko Pravo, 2022)
Although landlocked, Switzerland realised early on that having its own flag would be beneficial for the country to secure trade in times of peace and especially in times of war. Besides the fleet, it was important to have its own legislation. Maritime navigation is codified in the Federal Act on Maritime Navigation under the Swiss Flag (MNA). The Act takes over the Hague Rules in a modified form, as the Rules themselves allow, and the Visby Protocol. In a conflict of laws between the Hague Rules and the MNA, the national law has priority. The MNA regulates the flag legislation and the registration of ships, the organisation of the relevant authorities, the operation of maritime shipping, the contracts for the use of a seagoing vessel, and many other issues in this context. It will always apply if Swiss law is applicable under the rules of the Federal Code on Private International Law (CPIL). Swiss federal legislation applies exclusively on Swiss seagoing vessels on the high seas. In territorial waters, it also applies on board Swiss seagoing vessels, unless the coastal State declares its legislation to be mandatory. Insofar as the MNA contains no special provisions, the Swiss Code of Obligations applies to contracts for the use of a seagoing ship. The MNA regulates the charter parties as well. However, this is a sui generis contract and differs from both the contract of carriage and the contract on mandate. Currently, Swiss authorities are reconsidering the conditions for registering ships. Their endeavours will hopefully lead to the flagging-in into the Swiss registry again, which will expand the influence of Swiss maritime legislation.